(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the pedagogical possibilities of teaching the subject of inclusive education in the context of a digital educational environment from both theoretical and practical perspectives. It substantiates that the processes of digital transformation in the education system create the need for new didactic approaches, interactive methods, and the formation of individual learning trajectories. The effectiveness of using digital platforms, distance learning technologies, multimedia tools, and adaptive learning systems in teaching inclusive education is also discussed.